Identification of the types and characteristics of marine debris in Manado Bay, North Sulawesi Province - Lepar, Meita Jeane Wini; Tumbal, James; Mandagi, Conny M.; Timpal, Tartius; Mait, Nicolaas H.; Rompas, Vonny O.; Undap, Timothy; Kusen, Janny D. (Jurnal Ilmiah PLATAX, 2026)
This study analyses the spatial distribution and composition of marine debris in Manado Bay and discusses implications for coastal management strategies. Shoreline surveys across multiple sites assessed item counts, weight, material types and seasonal variation. The results of the analysis at Buloh Coast and Molas Coast, showed striking differences in the composition and density of marine garbage. On the Buloh coast, wood dominates with the highest density, especially in Transek 4 (85 grams/m2) and Transek 5 (57 g/m2), while plastics are also very significant, especially on Transek 5, with a very high density (86 gram/m2). On the other hand, on the Molas coast the wood remains the dominant type of garbage with the largest density at Transek 4, (51 g/ m2), but plastics show greater variation and do not reach the density as high as Buloh Coast, with the maximum density being at Transak 4, (48 g / m2). For plastic foam, the densities at Buloh Beach are relatively higher at Transec 5 (30 grams / m2) compared to Molas Coasts, where the greatest densities are at the Transek 2 (28 g /m2). Meanwhile, the glass and ceramic densities in Molas Beach are relatively higher at the transek (40 grams) compared with the Buloh coasts, the latter showing lower glass density and ceramic data. Results indicate plastics dominate debris composition, with seasonal peaks associated with rainfall and riverine inputs. Management recommendations include source reduction, improved solid-waste services, community engagement, and long-term monitoring to inform policy. Keywords: Marine debris, coastal management, Manado Bay, waste distribution, plastic pollution.